Capitalizing on the hydrophobic bias of electrospray ionization through chemical modification in mass spectrometry-based proteomics. (June 2011) - Shuford, Christopher M; Muddiman, David C
Protein chemical derivatization has emerged as an invaluable bioanalytical approach in mass spectrometry-based proteomics with nearly unlimited potential. To date, derivatization strategies in proteomics have primarily focused on improving mass spectral identification and relative quantification of proteins, as well as increasing enrichment yield from complex mixtures. However, there is a great opportunity to develop and exploit front-end chemical processes to enhance the ability to detect low-abundant peptides and proteins for a large number of applications. The content of this article focuses on improvements in targeted, mass spectrometry-based proteomic strategies, achieved by taking advantage of the mechanism of ESI through the use of hydrophobic chemical derivatization.